THE EFFECT OF LEADERSHIP STYLE AND JOB SATISFACTION ON EMPLOYEES' ORGANIZATIONAL COMMITMENT AT THE BAPPEBTI WAREHOUSE RECEIPT SYSTEM AND COMMODITY AUCTION MARKET DEVELOPMENT AND DEVELOPMENT BUREAU - Mutia Endang Novianti; Zulkifli Rangkuti; Jamal Hanaffy (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to determine the influence of leadership style and job satisfaction on the organizational commitment of employees of the warehouse receipt system development and development bureau and commodity auction market of BAPPEBTI. The phenomenon underlying this study is the discovery of employees with a suboptimal level of organizational commitment. In this study, the author used quantitative research. The population in this study was 145 employees. In this study, the author used a sampling technique using the Slovin formula for 59 employees. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study indicate that partially and simultaneously, the influence of leadership style and job satisfaction has a positive and significant effect on employee organizational commitment. This study emphasizes the importance of being able to follow up with appropriate policies to be able to optimally increase employee organizational commitment.